Security Analysis of Data Storage in Cloud-Based Digital Archive Management Systems - Meri Nova Marito Br Sipahutar; Ade Linhar P; Sardo Pardingotan Sipayung (Department of Informatics, Universitas Malikussaleh, 2025)
In today's global era, archive management plays a crucial role in supporting operational efficiency and informed decision-making. The adoption of cloud computing offers an innovative solution for managing digital archives more effectively and efficiently. This journal discusses the implementation of cloud computing in digital archive management using MySQL as a relational database management system. Through this approach, archive data can be stored, accessed, and managed more securely while ensuring data integrity. The study also explores the advantages of MySQL in terms of performance, scalability, and ease of access. Implementation of this system in several organizations has shown significant improvements in archive management efficiency and a reduction in operational costs. This system helps organizations manage their digitized data effectively by utilizing cloud computing as a more affordable and reliable storage solution